Derived Water Quality and Trophic State Indices for Lacustrine Systems of the Yucatán Peninsula during the Dry Season (April 2024) - Hernández Hernández, Plutarco (PANGAEA, 2026)
This dataset compiles derived water quality indicators for multiple lacustrine systems across the Yucatán Peninsula during the dry season of April 2024. Sampling locations correspond to inland lakes distributed across a karstic low-relief landscape strongly influenced by the regional aquifer system. Using physicochemical, nutrient, and biological measurements obtained during the Water Quality Monitoring Campaign, integrated indicators were calculated to evaluate ecosystem condition. These include the Water Quality Index (WQI), the Carlson Trophic State Index (TSI), trophic state classification, and the nitrogen-to-phosphorus (N) ratio used to infer the potentially limiting nutrient for primary productivity. Geographic coordinates and sampling dates are provided for each site to facilitate spatial analysis. The dataset enables the assessment of trophic conditions, nutrient limitation patterns, and overall water quality status across inland aquatic ecosystems of the Yucatán Peninsula during the dry season, providing a baseline for regional limnological monitoring and comparative ecological studies.
Keywords: biochemical oxygen demand; chlorophyll-a; Conductivity; Dissolved oxygen; Nitrogen; pH; Phosphate; Temperature; total coliforms; turbidity